The Significance of Al-Ghazali's Maslahah Concept to the Development of Usul Fiqh and Islamic Law - Yeni Mafiah; Tri Wahyu Hidayati (AN NUR: Jurnal Studi Islam, 2023)
The purpose of this research was to examine the significance of al-Ghazali's ma?la?ah concept to the development of u??l fiqh and Islamic law. This research method was qualitative with descriptive analytic presentation and the research type was library research. The research result showed that the concept of ma?la?ah al-Ghazali was used in solving problems of Islamic law because the principle in ma?la?ah was maintaining the objectives of Islamic law (maq??id al-syar?‘ah), covering religion, soul, mind, lineage, and property. There were six points of significance of al-Ghazali's ma?la?ah concept in the development of u??l fiqh and Islamic law, namely, the important role of al-Ghazali's ma?la?ah concept in u??l fiqh and Islamic legal thought, al-Ghazali's rejection of the concept of ma?la?ah, al-Ghazali's ma?la?ah had no basis in nas, al-Ghazali's emphasized on preserving the objective objectives of Islamic law, al-Ghazali's ma?la?ah as a tool to weigh the benefits and losses of an action or decision, and al-Ghazali's ma?la?ah determined whether or not an action or decision was permissible. This concept helped the ulama to make decisions that were in line with the principles of Islamic law.